2018
DOI: 10.3895/actio.v3n3.7998
|View full text |Cite
|
Sign up to set email alerts
|

Problematizando o ensino de modelos atômicos: uma exploração sobre as representações e o uso de um jogo didático

Abstract: O presente trabalho busca discutir sobre o ensino de modelos atômicos no ensino médio, a partir do uso de diversificados recursos didáticos, buscando-se superar algumas das dificuldades atreladas ao processo ensino-aprendizagem deste conteúdo. Para tal, planejou-se uma sequência de aulas em que se explorou o uso de representações mentais, modelos e um jogo didático. O planejamento foi realizado por licenciandas em química e aplicado com alunos do primeiro ano do Ensino Médio em uma escola estadual de Joinville… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Finally, it was concluded that part of the students, regardless of being able to express themselves correctly when approaching the subject of atom structure with the nucleus and electrosphere, have questions when applying in daily situations where it is necessary to master these concepts. In this context, Camargo et al (2018) emphasize that the use of models and abstractions is among the main difficulties related to the teaching of atomic models. This difficulty, according to them, is due to the fact that the study of the atom involves the submicroscopic level, that is, it is something that is not possible to be touched or visualized.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it was concluded that part of the students, regardless of being able to express themselves correctly when approaching the subject of atom structure with the nucleus and electrosphere, have questions when applying in daily situations where it is necessary to master these concepts. In this context, Camargo et al (2018) emphasize that the use of models and abstractions is among the main difficulties related to the teaching of atomic models. This difficulty, according to them, is due to the fact that the study of the atom involves the submicroscopic level, that is, it is something that is not possible to be touched or visualized.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, it was noticed a need to understand several concepts involved in the learning of intermolecular forces, such as chemical reaction, chemical bonds, attraction and repulsion, and energy exchanges. It is important to consider that when the student does not master these concepts, there is a reflection on the application of knowledge in different contexts and that this difficulty in comprehending the chemical contents by students, in general, is owing to the fact that Chemistry it is studied in a fragmented form, involving abstract concepts and highly specific symbolic language (Camargo et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Nesse caso, nota-se a necessidade de compreensão de vários conceitos envolvidos na aprendizagem de forças intermoleculares, tais como: reação química, ligações químicas, atração e repulsão, trocas de energia. É importante considerar que quando o estudante não domina esses conceitos, ocorre um reflexo na aplicação do conhecimento em diferentes contextos, e, que essa dificuldade na compreensão dos conteúdos químicos por parte dos alunos, de modo geral, deve-se ao fato de a Química ser estudada de maneira fragmentada, envolvendo conceitos abstratos e linguagem simbólica bastante específica (Camargo et al, 2018).…”
Section: Resultsunclassified